Peran Internet Of Thing Dalam Perpajakan Indonesia - Tia Mahrurotul Fikriyah; Tony Agusta; Dwi Suhartini (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2023)
Technology in the field of taxation continues to develop from time to time. One of the newest technologies is the internet of things. This study intends to reveal the role of the internet of things in the taxation sector. The type of research used is qualitative research through the literature review method. Data was collected using the Google Scholar search engine. The results of the study concluded that the Internet of Things (IoT) is an important part of the development of tax technology. This supports the goal of the Directorate General of Taxes to use Big Data Analytics which can optimize digital tax potential through 2 mechanisms, namely predictive analysis and secondly through tax ranking. Keywords: Technology, Taxes, Internet of things